2019
DOI: 10.1111/jbi.13560
|View full text |Cite
|
Sign up to set email alerts
|

Could coastal plants in western Amazonia be relicts of past marine incursions?

Abstract: The rainforests of Amazonia comprise some of the most biologically diverse ecosystems on Earth. Despite this high biodiversity, little is known about how landscape changes that took place in deep history have affected the assembly of its species, and whether the impact of such changes on biodiversity can still be observed. Here, we present a hypothesis to explain our observation that plants typical of Neotropical coastal habitats also occur in western Amazonia, in some cases thousands of kilometres away from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…Amazon, Guiana Shield, marine incursions, Orinoco, Paleogeography, Parana-Paraguay, Pebas Wetlands, South America F I G U R E 1 Map of South America during the middle Miocene showing position of the Pebas Wetlands (adapted from Hoorn, Wesselingh, Ter Steege, et al, 2010. using shapefiles from Cao et al, 2017 (Aleman & Ramos, 2000;Brea & Zucol, 2011), while others argue that it extended only as far as present-day Bolivia (Bernal et al, 2019;Wesselingh & Hoorn, 2011). The giant wetlands of the Pebas experienced oscillating levels of marine influence, as evidenced by sediments characteristic of both freshwater and tidal conditions (Hovikoski et al, 2010) and a rich fossil record of freshwater to marine-associated lineages, ranging from invertebrates (Wesselingh et al, 2006;Wesselingh & Ramos, 2010) and plants (Bernal et al, 2019;Hoorn, 2006), to crocodylians (Salas-Gismondi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amazon, Guiana Shield, marine incursions, Orinoco, Paleogeography, Parana-Paraguay, Pebas Wetlands, South America F I G U R E 1 Map of South America during the middle Miocene showing position of the Pebas Wetlands (adapted from Hoorn, Wesselingh, Ter Steege, et al, 2010. using shapefiles from Cao et al, 2017 (Aleman & Ramos, 2000;Brea & Zucol, 2011), while others argue that it extended only as far as present-day Bolivia (Bernal et al, 2019;Wesselingh & Hoorn, 2011). The giant wetlands of the Pebas experienced oscillating levels of marine influence, as evidenced by sediments characteristic of both freshwater and tidal conditions (Hovikoski et al, 2010) and a rich fossil record of freshwater to marine-associated lineages, ranging from invertebrates (Wesselingh et al, 2006;Wesselingh & Ramos, 2010) and plants (Bernal et al, 2019;Hoorn, 2006), to crocodylians (Salas-Gismondi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Pebas Mega‐Wetland System (hereafter Pebas wetlands or system) was an epicontinental marine/freshwater system covering more than one million km 2 , spanning from the Caribbean to southern South America (Figure 1; Bernal et al, 2019; Hoorn, Wesselingh, Hovikoski, et al, 2010; Hoorn, Wesselingh, Ter Steege, et al 2010; Shephard et al, 2010; Wesselingh & Hoorn, 2011). This system covered the western Amazon region during most of the Miocene (23–10 Ma) (Bernal et al, 2019; Hoorn, Wesselingh, Hovikoski, et al, 2010), but its southernmost boundary is uncertain. Some authors have suggested it extended as far as southern Argentina, connecting to the Paranaense Sea (Aleman & Ramos, 2000; Brea & Zucol, 2011), while others argue that it extended only as far as present‐day Bolivia (Bernal et al, 2019; Wesselingh & Hoorn, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The Pebas wetland might in fact have increased opportunities for dispersal and diversification of some typical coastal plants (Bernal et al 2019), including many of the butterflies’ hostplants in the region: mainly Aracaceae (palms), Poaceae (bamboo) and Zingiberales such as Marantaceae (Beccalconi et al 2008, Janzen et al 2009). Therefore, the evolutionary consequences of the Miocene marine incursions in western Amazonia might have been mixed, restricting dispersal and diversification in some lineages while providing ecological opportunities for others, such as Brassolini butterflies.…”
Section: Discussionmentioning
confidence: 99%
“…This wetland system was occasionally affected by marine flooding events, which were probably short-lived, and at least two dated events at ∼13.7 and ∼17.8 Mya (Jaramillo et al ., 2017a) were concurrent with the early and rapid cladogenesis events of major Brassolini clades in Amazonia. The Pebas wetland might in fact have increased opportunities for dispersal across Amazonia and diversification of some typical coastal plants (Bernal et al ., 2019), including many of the Brassolini’s hostplants in the region: Arecaceae (palms), Poaceae (bamboos), and Zingiberales such as Marantaceae (Beccaloni et al ., 2008; Janzen et al ., 2009). It is plausible that the evolutionary consequences of the Miocene marine incursions in western Amazonia might have been mixed and rather ephemeral (Musher et al ., 2019), restricting dispersal and diversification in some butterfly lineages such as Ithomiini (Chazot et al ., 2019b) while providing ecological opportunities for diversification of others, such as Brassolini.…”
Section: Discussionmentioning
confidence: 99%